DYNAMIC MULTI-STRUCTURE IN MODELLING A TRANSITION FLEXURAL WAVE. Issue 2 (5th December 2014) - Movchan, Alexander B.; Brun, Michele; Slepyan, Leonid I.; Giaccu, Gian F.
Abstract : This paper presents a model of a 1D–1D dynamic multi-structure, supporting propagation of a transition wave. It is used to explain the recent phenomenon of the collapse of the San Saba bridge. An analytical model is supplied with illustrative numerical simulations.